1994
DOI: 10.1029/93jc03334
|View full text |Cite
|
Sign up to set email alerts
|

Baroclinic flows, transports, and kinematic properties in a cyclonic‐anticyclonic‐cyclonic ring triad in the Gulf of Mexico

Abstract: During October‐November 1986 the baroclinic circulation of the central and western Gulf of Mexico was dominated by an anticyclonic ring that was being bisected by two north and south flanking cyclonic rings. The baroclinic circulation revealed a well‐defined cyclonic‐anticyclonic‐cyclonic triad system. The anticyclone's collision against the western gulf continental slope at 22.5°N, 97°W originated the north and south flanking cyclonic rings. The weakening of the anticyclone's relative vorticity, during the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 15 publications
2
21
0
3
Order By: Relevance
“…Typically, ocean cyclones are observed both south and north of vortices which impinge upon the western slope. For example, Vidal et al (1994) reported an anticyclone's interaction with the western CoM continental slope originated flanking cyclonic rings to the north and south of the colliding anticyclone. In cases where the vortex impinges strongly upon the western slope (which occurs more frequently in the GoM than the vortex initially over the northern slope, reported by Oey and Zhang (2004)), the 'collision' cyclone and the slope jet to the south would be stronger (as seen in Fig.…”
Section: Effect Of Strong Collisionmentioning
confidence: 99%
“…Typically, ocean cyclones are observed both south and north of vortices which impinge upon the western slope. For example, Vidal et al (1994) reported an anticyclone's interaction with the western CoM continental slope originated flanking cyclonic rings to the north and south of the colliding anticyclone. In cases where the vortex impinges strongly upon the western slope (which occurs more frequently in the GoM than the vortex initially over the northern slope, reported by Oey and Zhang (2004)), the 'collision' cyclone and the slope jet to the south would be stronger (as seen in Fig.…”
Section: Effect Of Strong Collisionmentioning
confidence: 99%
“…La circulación de agua en el Golfo de México está definida principalmente por la fuerte corriente proveniente del Mar Caribe que penetra por el Estrecho de Yucatán y forma la denominada Corriente del Lazo para salir hacia el Atlántico Norte por el Estrecho de la Florida (Vukovich 1988, Vidal et al 1994. Esta condición de circulación se suma a las características particulares del área de estudio donde dominan fondos de tipo kárstico, hay alta transparencia y parches de vegetación sumergida, la plataforma continental es extensa con una pendiente muy suave, de manera que en los sitios de muestreo la profundidad raramente supera los dos metros.…”
Section: Discussionunclassified
“…Se ha postulado que la presencia de los giros ciclónicos en la periferia de la Corriente de Lazo está asociada al desprendimiento del gran giro anticiclónico (Vukovich & Maul 1985). Sin embargo, se ha observado la formación de los giros ciclónicos sin que se presente el desprendimiento del giro anticiclónico; también, se ha propuesto que los giros ciclónicos pueden ser producidos por el choque de los anticiclónicos con la costa oeste del golfo (Hurlburt & Thompson 1980, Smith 1986, Vidal et al 1994, debido a la conservación de la vorticidad potencial (Hurlburt & Thompson 1982, Hamilton et al 1999, Ohlmann et al 2001, Villanueva et al 2002.…”
Section: Introductionunclassified